Performance measurement, reporting, obstacles and accountability : recent trends and future directions - Thomas, Paul, 1943- (ANSOG monographs, 2006)
"This monograph identifies the ways that 'politics' enters into the creation of performance measurement systems, the selection of the official and unofficial aims of such systems, the selection of performance criteria and measures, the interpretation of findings, the responses to such findings and the implications of performance reporting for the accountability of both politicians and public servants. Along the way, both the conditions favouring and the obstacles to successful performance measurement will be highlighted."--Publisher's description